Peran Konseling Pastoral Dalam Mengatasi Fatherless Pada Remaja Perempuan Usia (12-18 Tahun) - Rista (SAPA - Jurnal Kateketik dan Pastoral, 2025)
Parents have a very important role in the growth and development of children. Not only mothers but fathers are also very important. The figure of a father is also very much needed in educating children not only as the head of the household who works but also educates children, if a child does not feel the presence of a father figure in his life, it has a physical and psychological impact on him. Losing a father figure or the role of a father is also known as fatherless. Fatherless makes a person inferior and lonely. This research method uses descriptive qualitative through library research, namely collecting data by understanding and studying theories related to and supporting this research. The aim is to find out how the role of pastoral counseling in overcoming fatherlessness in adolescent girls aged 12-18 years. The results of this study indicate that adolescent girls who experience fatherlessness will have a very bad impact on their adolescence related to building relationships with the opposite sex, emotional disorders, identity crises, and behavioral disorders. Therefore, Christian counselors are present to help deal with adolescent girls who experience fatherlessness by; 1). Building relationships, 2). Having empathy, 3). Guiding, 4). Healing, 5). Exemplary function.